2017
DOI: 10.1002/jib.437
|View full text |Cite
|
Sign up to set email alerts
|

Production of bioethanol by facultative anaerobic bacteria

Abstract: There is increased interest in using facultative aerobic bacteria to produce bioethanol from waste materials, including complex hemicellulosic biomass. In this laboratory study, ethanol was produced by different facultative aerobic bacteria (Lactobacillus plantarum M24, Lactobacillus sakei LB49, Weissella viridescens LB37 and Pediococcus acidilactici M17) from diverse waste materials (corn, corncob, paper and pine cones). Of these, corn was found to be the best substrate for bioethanol production with L. plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Cellulose quality, temperature, aeration, carbon sources, incubation period, medium additives pH of the medium and presence of inducers are important parameters for the optimized production of cellulase enzymes. Other researchers have also reported cellulase production enhancement by the optimization of cultural conditions [28][29][30][31][32]. Thus, in the present study, quantitative estimation and optimization of the production of bioethanol with appropriate substrate, i.e, leaf, are required for the pilot scale and large-scale business.…”
Section: Production Of Bioethanolmentioning
confidence: 94%
“…Cellulose quality, temperature, aeration, carbon sources, incubation period, medium additives pH of the medium and presence of inducers are important parameters for the optimized production of cellulase enzymes. Other researchers have also reported cellulase production enhancement by the optimization of cultural conditions [28][29][30][31][32]. Thus, in the present study, quantitative estimation and optimization of the production of bioethanol with appropriate substrate, i.e, leaf, are required for the pilot scale and large-scale business.…”
Section: Production Of Bioethanolmentioning
confidence: 94%
“…Alcohol can be produced from biomass via thermochemical such as gasification and pyrolysis [46] or biochemical routes such as fermentation [47]. Emerging technology such as microbial synthesis in producing alcohol is also becoming attractive [48,49]. A conceptual schematic diagram showing these various processing strategies of jet fuel production from biomass is given in Figure 3.…”
Section: Alcohol-to-jet (Atj)mentioning
confidence: 99%
“…In addition to the rapid fermentation of carbohydrates, bacteria are also present in natural fermentable substrates as enlisted in Table 1. Soleimani et al (2017) has reported the possibility of producing ethanol from the bacteria Lactobacillus plantarum M24, Lactobacillus sakei and Weissella viridescens LB37 by using agricultural residues (corn, corn residues and pine leaves). The results of the study proved that L. plantarum M24 is the most efficient type of bacteria in ethanol production from agricultural waste.…”
Section: Bacteriamentioning
confidence: 99%